"Retronychia – clinical and pathophysiological aspects". (5th October 2015) - Ventura, F.; Correia, O.; Duarte, A.F.; Barros, A.M.; Haneke, E.
Abstract: Retronychia represents proximal ingrowth of the nail that occurs when the nail embeds backwards into the proximal nail fold. It is suspected when there is a persistent paronychia, particularly in the setting of trauma. Important clinical criteria for diagnosis are inflammation of the proximal nail fold, granulation tissue emerging from under the nail fold, thickening of the proximal portion of the nail plate and interruption of nail growth. The condition is rarely diagnosed and often misinterpreted, and is therefore unnecessarily treated with systemic antibiotics and antifungals. Avulsion of the nail confirms the diagnosis and it is the curative treatment. Conservative treatment with an adhesive technique is a valid option in early cases. We report 20 cases of retronychia diagnosed in our department between 2010 and 2013.